Prusko-niemieckie państwo prawa a polska mniejszość w Prusach (1815–1914) Stan badań i postulaty badawcze - Tarnowska, Anna (Studia Iuridica Toruniensia, 2012)
<!--[if gte mso 9]> <![endif]--> The author presents a new research project on the concept of the rule of law in the nineteenth century Germany, in view relative to the Polish national minority, living in the prussian provinces of Posen and Westpreussen. This paper presents the thesis and research perspectives, requiring extended analysis: such as the genesis and content of the Prussian-German concept of the rule of law or a question of system administration bodies and institutions of protection of fundamental rights. Finally, to obtain answer to a question about the degree of eff ective legal protection of Polish citizens in Prussia and the German Reich the analyze, even limited, the administrative and judicial practice is required element – especially jurisprudence of the administrative courts, including Oberverwaltungsgericht in Berlin. The author presents the current state of research into the history of Polish territories under Prussian rule, and the Prussian- German policy towards the Polish minority, the key position of a synthesis, monographs and minor papers. <!--[if gte mso 9]> Normal 0 21 false false false PL X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->